Efektivitas Musik Sholawat Sebagai Metode Dakwah di Kalangan Generasi Z - Dalimunthe, Mhd Alvin Habib; Soiman, Soiman (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
This study aims to evaluate the effectiveness of sholawat music as a method of da’wah among Generation Z at the Istiqlal Delitua Education Foundation. Generation Z, born between 1997 and 2012, is known to have grown up in the digital era and has a preference for media that is relevant to their daily lives. Sholawat music, which combines Islamic values ​​with touching melodies, has great potential as an effective da’wah tool. This study used a mixed method, namely a qualitative and quantitative approach. Qualitative data were obtained through in-depth interviews with students and teachers at the Istiqlal Delitua Foundation, while quantitative data were collected through a survey that measured students’ understanding, emotional responses, and behavioral changes towards sholawat music. The results showed that most students showed a high interest in sholawat music, which was considered pleasant and calming. As many as 85% of respondents said they enjoyed listening to sholawat music, 78% felt that sholawat music helped them understand Islamic teachings better, and 72% experienced positive changes in their daily behavior after regularly listening to sholawat music. In addition, 69% of respondents felt more motivated to participate in social and religious activities after listening to sholawat music. The study results showed that sholawat music’s effectiveness as a medium of da’wah reached an effectiveness level of 93%, indicating a very effective category.